2009
DOI: 10.1007/s10979-008-9148-6
|View full text |Cite
|
Sign up to set email alerts
|

Complex questions asked by defense lawyers but not prosecutors predicts convictions in child abuse trials.

Abstract: Attorneys' language has been found to influence the accuracy of a child's testimony, with defense attorneys asking more complex questions than the prosecution (Zajac & Hayne, J. Exp Psychol Appl 9:187-195, 2003; Zajac et al. Psychiatr Psychol Law, 10:199-209, 2003). These complex questions may be used as a strategy to influence the jury's perceived accuracy of child witnesses. However, we currently do not know whether the complexity of attorney's questions predict the trial outcome. The present study assesses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 19 publications
1
42
0
1
Order By: Relevance
“…The law knows how to criticize the interviewing performance of professionals who work outside the www.annualreviews.org • Interviewing Children courtroom, but it has been slow to reform how children are questioned inside the courtroom. Prosecutors' questions tend to be closed-ended, leading to unelaborated responses from children , Stolzenberg & Lyon 2014, and their questions are often unnecessarily difficult (Evans & Lyon 2012) and as complex as defense attorneys' (Evans et al 2009). Prosecutors frequently fail to ask children about their reasons for failing to disclose (or why they disclosed when they did), and they do little to teach jurors how abuse perpetrators' behavior induces compliance and silence (Stolzenberg & Lyon 2014).…”
Section: Implications For the Legal Systemmentioning
confidence: 99%
“…The law knows how to criticize the interviewing performance of professionals who work outside the www.annualreviews.org • Interviewing Children courtroom, but it has been slow to reform how children are questioned inside the courtroom. Prosecutors' questions tend to be closed-ended, leading to unelaborated responses from children , Stolzenberg & Lyon 2014, and their questions are often unnecessarily difficult (Evans & Lyon 2012) and as complex as defense attorneys' (Evans et al 2009). Prosecutors frequently fail to ask children about their reasons for failing to disclose (or why they disclosed when they did), and they do little to teach jurors how abuse perpetrators' behavior induces compliance and silence (Stolzenberg & Lyon 2014).…”
Section: Implications For the Legal Systemmentioning
confidence: 99%
“…They may face the challenge of deciphering legal jargon, as well as linguistically complex questions that they are ill equipped to answer (as are many adults; Carter, Bottoms, & Levine, 1996;Perry et al, 1995). However, this might not undermine children's credibility, as one study of trial transcripts found that complex questions asked by defense attorneys predicted convictions, rather than acquittals in those cases (Evans, Lee, & Lyon, 2009). Nevertheless, children also may be required to offer testimony on concepts that are developmentally beyond their reach.…”
Section: Communication and Linguistic Abilitymentioning
confidence: 99%
“…Prior research has not directly explored these issues. It is likely, though, that there is wide variation in use of temporal structure across attorneys and cases, just as there is wide variation in attorney question complexity and question type (e.g., Evans, Lee, & Lyon, ; Klemfuss et al ., ; Zajac & Hayne, ). These variations may affect both children's responses and case outcomes.…”
Section: Introductionmentioning
confidence: 99%